Network Meta-analysis of Randomized Controlled Trials Assessing Neuromodulation Therapies for Painful Diabetic Neuropathy - Li Li; Xueqin Luo; Yong Liu; Yongjie Jiang; Yankun Chen; Yangmei Chen; Jinping Wang (Neurology and Therapy)
Abstract Introduction Neuromodulation therapies (including non-invasive and invasive neuromodulation) are being used to treat painful diabetic neuropathy (PDN). Methods A systematic search of the PubMed, Embase, Cochrane Library, Web of Science, and Scopus databases was conducted, from their inception until 1 October 2024, to identify randomized controlled trials (RCTs) on neuromodulation therapies for PDN. Data were collected on pain intensity of various adjunctive therapies for PDN, including transcutaneous electrical nerve stimulation (TENS), percutaneous electrical nerve stimulation, repetitive transcranial magnetic stimulation, pulsed electromagnetic field therapy, spinal cord stimulation (SCS), transcranial direct current stimulation, frequency rhythmic electrical modulation system, mesodiencephalic modulation, and sham. Results The data from an aggregate of 12 separate studies, comprising a total sample size of 922 participants, was subject to analysis. All seven neuromodulation therapies exhibited better outcomes in pain intensity compared to the Sham intervention, with TENS achieving the highest ranking, followed by SCS. At the final follow-up time point, statistically significant reductions in pain intensity (vs. Sham) was only observed for SCS. Conclusion The results of this network meta-analysis should facilitate the development of clinical guidance and enhance the decision-making process for both patients and healthcare professionals, thereby identifying the most appropriate PDN treatment options. Trial Registration PROSPERO: CRD42024597208.